RANCANGAN PROGRAM INTEGRATED MARKETING COMUNICATION (IMC) RS NAILI - Try Wulan Sari; Rima Semiarty (Procuratio : Jurnal Ilmiah Manajemen, 2020)
Integrated Marketing Communication (IMC) is a promising communication concept, more than just integration, coordination and unification of communication instruments. IMC has great potential in influencing business performance, to provide a competitive advantage to companies, to increase brand equity, and to ensure the effectiveness and consistency of communication by facilitating the achievement of communication and marketing objectives. This research is a type of qualitative research using the Grounded Theory method conducted at the Naili DBS Hospital in April to December 2019. The results of this study was IMC program design of the Naili DBS Hospitalthrough eight parameters such as advertising where hospitals can carry out internet advertisements containing testimonials or endorsements as well as billboard installations, sales promotion can be carried out through consumer loyalty programs where hospitals form consumer communities in order to facilitate the implementation of sales promotions. Sales people in personal selling can sell to FKTP because 89% of Naili DBS Hospital patients are BPJS Health participants. For public relations / publicity it is better to hold a seminar and create a company magazine, for the parameters of hospital wom can create marketing from patients to deliver their experiences to others, this also relates directly to the implementation of direct marketing in which many customers have formed word of mounth no paid at Naili DBS Hospital. Interactive marketing must be re-enforced in order to be widely known by patients. The event and experience can be held by public exhibition in the form of seminars to introduce the Naili DBS Hospital to the public. Integrated Marketing Communication (IMC) merupakan konsep komunikasi yang menjanjikan, lebih dari sekadar integrasi, koordinasi, dan penyatuan instrumen komunikasi.IMC berpotensi besar dalam mempengaruhi kinerja bisnis, untuk memberikan keunggulan kompetitif pada perusahaan, untuk meningkatkan ekuitas merek, dan untuk memastikan efektivitas dan konsistensi komunikasi dengan memfasilitasi pencapaian komunikasi dan tujuan pemasaran.Penelitian ini merupakan jenis penelitian kualitatif dengan metode Grounded Theory yang lakukan di RS Naili DBS pada bulan April sampai dengan Desember 2019. Hasil dari penelitian ini berupa rancangan program IMC RS Naili DBS melalui delapan parameter yaitu advertising dimana rumah sakit dapat melaksanakan iklan internet yang berisikan testimony atau endorsement serta pemasangan billboard, sales promotion dapat dilaksanakan melalui program loyalitas konsumen dimana rumah sakit membentuk komunitas – komunitas konsumen agar memudahkan dalam pelaksanaan promosi penjualan. Sales people dalam personal selling dapat melakukan penjualan kepada FKTP dikarenakan 89 % pasien RS Naili DBS adalah peserta BPJS Kesehatan. Untuk public relation/ publicity sebaiknya dilaksanakan seminar dan membuat majalah perusahaan, untuk parameter wom rumah sakit dapat membentuk marketing – marketing baru dari para pasiennya agar menyampaikan pengalamannya kepada orang lain, hal ini juga berhubungan langsung dengan pelaksanaan direct marketing dimana sudah terbentuk banyak pelanggan yang melakukan word of mounth no paid di RS Naili DBS. Interactive marketing belum dikenal banyak oleh pasien sehingga harus di tinggatkan kembali pelaksanaannya.Pelaksanaan event and experience dapat dilakukan pameran publik berupa seminar – seminar untuk lebih mengenalkan lagi RS Naili DBS kepada masyarakat.